Comparative evaluation of progression rate in keratoconus before and after collagen crosslinking. Issue 8 (9th November 2017) - Wang, Yu Meng; Chan, Tommy CY; Yu, Marco C Y; Jhanji, Vishal
Abstract : Purpose: To compare the rate of disease progression in keratoconus before and after corneal collagen crosslinking (CXL). Methods: 145 eyes were followed without CXL (no-CXL group) for a median duration of 31 months whereas 45 eyes were followed up for 41 months before (pre-CXL) and after (post-CXL) accelerated, epithelium-off crosslinking. Progression was defined based on significant slope found in linear mixed effect models against time. Swept-source optical coherence tomography was used for measurement of anterior steep keratometry, anterior flat keratometry (Ant Kf), anterior average keratometry (Ant Avg K); posterior steep keratometry, posteriorflat keratometry (Post Kf), posterior average keratometry (Post Avg K) and corneal thickness. Results: The patients in pre-CXL group were significantly younger (26.3±5.48 years) compared with the patients in no-CXL group (32.7±10.24 years) (P=0.004). Significant differences were observed during baseline examination for all parameters (P≤0.035) between pre-CXL and no-CXL groups except Ant Cyl and Post Cyl. During observation period, statistically significant differences were noted between pre-CXL and no-CXL groups in the progression rate of Ant Kf, Ant Avg K, Post Kf and Post Avg K (P≤0.045). After CXL, the progression rate in post-CXL group was comparable to that in no-CXL group. All corneal parameters remained stable in no-CXL group throughout the follow-up period. Conclusions: Serial tomographic examination is useful to document disease progression before and after CXL. In our study, a decrease in progression rate of corneal parameters was noted after CXL. In cases with stable corneal parameters over time, careful monitoring can be considered instead of collagen crosslinking.